Studies of oxygen reduction activity and stability of carbon-supported PdNi and PdCu nanoparticles of different compositions - Khan, Muhammad Sufaid [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The slow kinetics of the oxygen reduction reaction is the main cause of the severe performance losses of fuel cell cathode. Pt is the most active pure metal to catalyze this reaction. However, because of their limited availability and high price, the use of cheaper metals to act as catalysts in fuel cell electrodes is highly desirable. In this context, Pd-based catalysts are getting increasing attention. Thus, the main objective of this work was to study the oxygen reduction reaction on carbon-supported PdM (M = Ni, Cu) catalysts with different atomic ratios (Ni and Cu 10-50% in atoms), in acidic and alkaline solutions. The modified polyol method was used for the preparation of PdM nanoparticles that were then supported on carbon powder. The catalysts were characterized by X-ray diffraction (XRD) to investigate the crystalline structure and by X-ray absorption spectroscopy (XAS) to examine the electronic properties. The electrochemical behavior was studied by cyclic voltammetry. The PdNi/C and PdCu/C catalyst and a Pd/C reference sample were evaluated as electrocatalysts for the oxygen reduction reaction in acidic and alkaline solutions using the rotating ring disk electrode technique. Results showed formation of PdM alloys and an increase in the electronic occupation of the Pd 4d band. In both media, all PdM/C samples were more active for oxygen reduction than Pd/C, with activity increasing as the percentage of Ni or Cu increased. The production of hydrogen peroxide was small indicating that the reduction of oxygen proceeds mainly via the four-electron path. PdCu/C catalysts were more active than PdNi/C materials in acidic medium, but PdNi/C samples had better performance in alkaline solution. In addition, stability tests revealed that the presence of Ni and Cu considerably decreases the dissolution of Pd in acidic medium, although the stability of the materials was lower in alkaline than in acidic medium.

A cinética lenta da reação de redução de oxigênio é a principal causa das severas perdas de desempenho dos catodos de células a combustível. A Pt é metal puro mais ativo para catalisar esta reação. Entretanto, devido sua baixa abundância e alto custo, o uso de metais mais baratos para atuar como catalisadores nos eletrodos de células a combustível é muito desejável. Neste contexto, catalisadores baseados em Pd têm atraído cada vez mais atenção. Assim, o principal objetivo deste trabalho é estudar a reação de redução de oxigênio em catalisadores PdM (M = Ni, Cu) com diferentes composições (Ni e Cu 10-50% em átomos), em soluções ácidas e alcalinas. O método do poliol modificado foi utilizado para preparar as nanopartículas PdM, que foram posteriormente suportadas em pó de carbono. Os catalisadores foram caracterizados por difração de raios X para investigar a estrutura cristalina e por espectroscopia de absorção de raios X para determinar as propriedades eletrônicas. O comportamento eletroquímico foi examinado por voltametria cíclica. Os materiais PdNi/C e PdCu/C, assim como uma amostra de Pd/C usada como material de referência, foram testados como eletrocatalisadores para a reação de redução de oxigênio em meio ácido e alcalino utilizando a técnica do eletrodo de disco-anel rotatório. Os resultados mostraram formação de ligas PdM e um aumento na ocupação eletrônica da banda 4d do Pd. Em ambos os meios, os materiais PdM/C se mostraram mais ativos para a redução de oxigênio que o Pd/C, com atividades que aumentam à medida que cresce a percentagem de Ni or Cu. A produção de peróxido de hidrogênio foi baixa, indicando que a redução de oxigênio ocorre principalmente via 4 elétrons. Os catalisadores PdCu/C se mostraram mais ativos que os de PdNi/C em meio ácido, mas as amostras de PdNi/C foram mais ativas em meio alcalino. Além disso, testes de estabilidade revelaram que a presença de Ni ou Cu diminui consideravelmente a dissolução de Pd em meio ácido, mas a estabilidade destes materiais em meio básico é menor que em ácido.
Estudos da atividade para redução de oxigênio e da estabilidade de nanopartículas de PdNi e PdCu de diferentes composições suportadas em carbono
Keywords: Oxygen reduction reaction; Pd-based catalysts; PdM nanoparticles; Electrocatalysis; Fuel cell cathode; Redução de oxigênio; Catalisadores baseados em Pd; Nanopartículas PdM; Eletrocatálise; Cátodo